2018
DOI: 10.3390/ijms19020551
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effects of Cinnamic Aldehyde in an MPTP Mouse Model of Parkinson’s Disease

Abstract: Cinnamic aldehyde (CA), a key flavor compound in cinnamon essential oil, has been identified as an anti-oxidant, anti-angiogenic, and anti-inflammatory material. Recently, the neuroprotective effects of CA have been reported in various neurodegenerative disorders, including Parkinson’s disease (PD). In neurons, autophagy is tightly regulated, and consequently, the dysregulation of autophagy may induce neurodegenerative disorders. In the present study, we found that the selective dopaminergic neuronal death in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…TCA is a major active component of cinnamon that was shown to have antioxidant, cholesterol-lowering, antineoplastic, antibacterial, and antifungal properties. The potential therapeutic effects of TCA were also studied in several disease models of neurodegeneration, including 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced Parkinson’s disease [ 9 ] and 6-hydroxydopamine-induced dopaminergic injury models [ 10 ]. However, no studies examined whether TCA, a single compound derived from cinnamon, might be an effective therapeutic in AD.…”
Section: Introductionmentioning
confidence: 99%
“…TCA is a major active component of cinnamon that was shown to have antioxidant, cholesterol-lowering, antineoplastic, antibacterial, and antifungal properties. The potential therapeutic effects of TCA were also studied in several disease models of neurodegeneration, including 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced Parkinson’s disease [ 9 ] and 6-hydroxydopamine-induced dopaminergic injury models [ 10 ]. However, no studies examined whether TCA, a single compound derived from cinnamon, might be an effective therapeutic in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Chung, J. et al showed that cinnamic aldehyde could induce autophagy in macrophages. Another study demonstrated that cinnamic aldehyde exerts a neuroprotective effect in a Parkinson's disease model through autophagy inhibition 143 .…”
Section: Resultsmentioning
confidence: 99%
“…CA which is the major constituent of cinnamon oil exhibits a wide range of biological activities, including antipyretic, antitumoral, antibacterial, antidiabetic, anti-inflammatory, and antioxidant activities (Chew et al 2010;Kim et al 2006;Koh et al 1998;Lv et al 2017;Nour et al 2018;Sharma et al 2018;Shaughnessy et al 2001;Xue et al 2011;Zhu et al 2017). It also reportedly exerts neuroprotective effects against cerebral ischemia (Chen et al 2016;Zhao et al 2015), glutamate excitotoxicity (Lv et al 2017), and neurodegenerative diseases such as Alzheimer's and Parkinson's diseases (Bae et al 2018;George et al 2013), and it also has anti-neuroinflammatory effects on neuronal cell cultures (Bae et al 2018;Fu et al 2017;Ho et al 2013;Shi et al 2017;Yang et al 2016), as well as vasorelaxant effects on the isolated rat aorta (Alvarez-Collazo et al 2014;Xue et al 2011;Yanaga et al 2006), mesenteric artery (Veras et al 2013), mouse ear artery (Aubdool et al 2016), and porcine coronary artery (Raffai et al 2014), and in cerebral arteries (Earley et al 2009). Because of these neuroprotective and vasodilatory effects, we hypothesized that CA potentially exerts protective effects against SAH-induced EBI and vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…It reportedly exhibits various therapeutic properties (Xue et al 2011), including antitumoral, antipyretic, antimicrobial, antidiabetic, antimutagenic, antioxidant, and anti-inflammatory activities (Chew et al 2010;Kim et al 2006;Koh et al 1998;Lv et al 2017;Nour et al 2018;Sharma et al 2018;Shaughnessy et al 2001;Xue et al 2011). Numerous studies have shown that CA exhibits potent neuroprotective activity, inhibiting neuroinflammation, oxidative stress, and apoptosis (Bae et al 2018;Chen et al 2016;Fu et al 2017;Ho et al 2013;Lv et al 2017;Pyo et al 2013;Shi et al 2017;Yang et al 2016;Zhao et al 2015). Its vasodilator effects have also been widely studied and demonstrated in various vessels, such as the mouse ear artery (Aubdool et al 2016), rat aorta (Alvarez-Collazo et al 2014;Xue eet al 2011;Yanaga et al 2006), mesenteric artery (Veras et al 2013), and porcine coronary artery (Raffai et al 2014), as well as in cerebral arteries (Earley et al 2009).…”
Section: Introductionmentioning
confidence: 99%